On the Themes and Ideas of the Lyrical Heritage of Is’hoqkhon Tora Ibrat (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article condemns the vices of injustice, ignorance, and deceit that are criticized in the poet's lyrics. It is said that Ibrat's lyrics are written on enlightening, political, and social philosophical topics.